Dampak Penggunaan Game Online Terhadap Perilaku Bahasa Anak Usia Dini Di Kecamatan Lubuk Pakam Kabupaten Deli Serdang Sumatera Utara - Padilah, Padilah; Nashrillah, Nashrillah (UIN Sultan Maulana Hasanudin Banten, 2024)
This online game is an extraordinary magnet that makes children forget themselves, even including the language and words they communicate are very inappropriate to hear. This study aims to determine the impact of online game users on the language behavior of early childhood. The method used in this study is descriptive qualitative. Data collection techniques are obtained through interviews, observations, and documentation. Data analysis techniques use domain analysis with data reduction, data presentation, and data verification to draw conclusions. The focus of this study discusses how the impact of online game users on the language behavior of early childhood. The results of this study indicate that online games also have negative impacts, namely creating an addictive effect on playing online games, reducing the sense of socialization with people around them, and can cause psychological disorders caused by defeat when playing online games. Online games also have an impact on children's language behavior, both changes in attitudes or behavior from online games, children become more emotional, there are changes in speaking and often say rude things to friends and parents. They can learn these words from virtual interactions when they play online games.